2020
DOI: 10.9779/pauefd.540142
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye (5-8. Sınıflar) ve Singapur (P5-6., S1-2. Sınıflar) Matematik Öğretim Programlarının Cebir Öğrenme Alanı Bağlamında Karşılaştırılması

Abstract: Bu araştırmanın amacı Türkiye 5-8. sınıflar ile aynı sınıflar düzeyindeki Singapur matematik öğretim programlarının cebir öğrenme alanı bağlamında karşılaştırılmasıdır. Bu amaçla, ilgili programlar cebir öğrenme alanının alt öğrenme alanları ve işlendikleri sınıf düzeyleri ve içeriğin uygulama yönergeleri ve Bloom taksonomisinde yer aldığı basamaklara göre sınıflandırılması bakımlarından karşılaştırılmıştır. Araştırmada doküman incelemesi tekniği kullanılmıştır. Dokümanların incelenmesinde her iki ülkenin öğre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(2 reference statements)
0
0
0
1
Order By: Relevance
“…In this section, the studies conducted in Turkey between 2002-2021 comparing the mathematics curriculum of Turkey and other countries are examined; A total of 29 academic studies, including 11 articles (Altıntaş & Görgen, 2014;Bacakoğlu & Işık-Tertemiz, 2021;Batur et al, 2021;Bozkurt et al, 2020;Çiçek et al, 2021;Erdoğan et al, 2016;Güzel et al, 2010;Kul & Aksu, 2016;Sugandi & Delice, 2014;Tan-Şişman & Karataşlı, 2020;Yağan, 2020) and 18 master's theses (Abid, 2017;Böke, 2002;Çetinbağ, 2019;Çoban, 2011;Duygu, 2013;Erbilge, 2019;Galo, 2008;Güzel, 2010;Ismail-Amet, 2021;Karakaya, 2021;Karataşlı, 2019;Kaytan, 2007;Özkan, 2006;Öztürk, 2020;Serçe, 2020;Sugandi, 2015;Tezcan, 2016;Uğur-Arslan, 2015), were found. In these studies, it was found that 4 master's theses (Güzel, 2010;Sugandi, 2015;Tezcan, 2016;Karataşlı, 2019) were presented as articles (Bozkurt et al, 2020;Güzel et al, 2010;Tan-Şişman & Karataşlı, 2020;Sugandi & Delice, 2014) at the same time. Among these four studies conducted as both thesis and article, the thesis was considered.…”
Section: The Number Of Comparative Education Studies For Mathematics ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the studies conducted in Turkey between 2002-2021 comparing the mathematics curriculum of Turkey and other countries are examined; A total of 29 academic studies, including 11 articles (Altıntaş & Görgen, 2014;Bacakoğlu & Işık-Tertemiz, 2021;Batur et al, 2021;Bozkurt et al, 2020;Çiçek et al, 2021;Erdoğan et al, 2016;Güzel et al, 2010;Kul & Aksu, 2016;Sugandi & Delice, 2014;Tan-Şişman & Karataşlı, 2020;Yağan, 2020) and 18 master's theses (Abid, 2017;Böke, 2002;Çetinbağ, 2019;Çoban, 2011;Duygu, 2013;Erbilge, 2019;Galo, 2008;Güzel, 2010;Ismail-Amet, 2021;Karakaya, 2021;Karataşlı, 2019;Kaytan, 2007;Özkan, 2006;Öztürk, 2020;Serçe, 2020;Sugandi, 2015;Tezcan, 2016;Uğur-Arslan, 2015), were found. In these studies, it was found that 4 master's theses (Güzel, 2010;Sugandi, 2015;Tezcan, 2016;Karataşlı, 2019) were presented as articles (Bozkurt et al, 2020;Güzel et al, 2010;Tan-Şişman & Karataşlı, 2020;Sugandi & Delice, 2014) at the same time. Among these four studies conducted as both thesis and article, the thesis was considered.…”
Section: The Number Of Comparative Education Studies For Mathematics ...mentioning
confidence: 99%
“…It is seen that the studies examining mathematics curriculum outcomes in the context of comparative education mostly focus on similarities and differences in terms of content and scope (e.g., Böke, 2002;Çiçek, Kuzu, & Çalışkan, 2021;Duygu, 2013;Galo, 2008;Özkan, 2006). On the other hand, it has been determined that there are limited number of comparative studies examining from taxonomic aspects (e.g., Bozkurt, Çırak-Kurt, & Tezcan, 2020). On the study conducted by Weissbach (2018), the PISA results of Turkey and Germany until 2015 were compared and it was stated that Germany was close to the average of the Organization for Economic Cooperation and Development (OECD) in mathematics in 2000 and that its scores in all fields increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Karşılaştırmalı eğitim yöntemlerinden tanımlayıcı yaklaşım, doküman ve gözlem gibi ögelerden yararlanarak benzerlik ve farklılıkların tanımlanarak ortaya konmasını amaçlamaktadır (Demirel, 2000;Philips, 2006). Öğretim programlarının karşılaştırıldığı ülkeler, PISA TIMMS gibi uluslararası sınavlarda farklı sıralamalarda olabileceği gibi (Altıntaş ve Görgen, 2014;Bozkurt, Çırak Kurt ve Tezcan, 2019;Božić, Hasić, Jovanova ve Romano, 2018;Çetinbağ, 2019;Çiçek, Kuzu ve Çalışkan, 2021;Erbilge, 2019;Erbilgin, 2017;Kaytan, 2007;Yang, Tseng ve Wang, 2017;Yazıcıoğlu ve Pektaş, 2018) komşu veya ortak kültüre sahip ülkeler de (Amet, 2021;Hudayarova, 2019;Shuinshina, 2006) olabilmektedir. Türkiye öğretim programlarının diğer ülkelerin öğretim programlarıyla karşılaştırılması da bu yönüyle büyük önem arz etmektedir.…”
Section: Introductionunclassified
“…Cebirsel düşünme ise matematiği günlük hayatta işlevsel yapan önemli bir matematiksel düşünme biçimidir (Van De Walle, Karp ve Bay- Williams, 2012). Cebirsel düşünme becerisinin gelişimi ile matematikte bir üst seviyeye geçiş yapılarak hedeflenen başarıya ulaşılabilir (Bozkurt, Çırak Kurt ve Tezcan, 2020). Cebirsel düşünme becerileri düşük olan öğrenciler cebirsel denklemleri ve ifadeleri basitleştirmede, fonksiyon grafiklerini yorumlamada ve cebirsel problemleri çözmede başarısız olma eğilimindedir (Hajizah, Wijayanti ve Darhim, 2021).…”
unclassified